Effect of temperature and storage time on hen egg quality - Madrigal-Portilla, Jennifer; Salas-Durán, Catalina; Macaya-Quirós, Sofía (Agronomía Mesoamericana, 2023)
Introduction. The hen egg is a food of high nutritional value, with protein of high biological value and easy digestion, due to that it is indispensable to know what affects its quality when storing it. Objective. To evaluate the effect of temperature and days of storage on egg quality. Materials and methods. The trial took place between December 2019 and January 2020, in Palmares, Alajuela, Costa Rica. In two different moments, egg samples were taken from Hy Line Brown hens: 1000 eggs at the start of production (21 weeks of age) and 1000 eggs at peak of production (28 weeks of age). The eggs were stored at controlled (7-10 °C) and room ((18-26 °C) temperatures for up to 21 days. The following egg physical quality parameters were assessed: egg weight, eggshell thickness and resistance, Haugh units, and yolk color at 1, 4, 7, 14, and 21 days of storage, as well as a qualitative evaluation according to USDA standards (2000). Results. Egg weight was significantly lower at room temperatures and longer days of storage at peak production. Eggshell thickness and resistance presented a positive relationship with each other. Haugh units presented a significant decrease as storage days go by, with a higher negative slope for the eggs at room temperature. The storage temperature and days of storage degraded the perception and qualitative classification of eggs by the consumers, in higher proportion for the eggs at room temperature. Conclusion. Storage at room temperature and between 14 to 21 days were factors that affected the egg quality and the possible consumer’s perception towards this product.